Melindungi Kulit: Tinjauan Komprehensif tentang Tabir Surya Anorganik dan Perannya dalam Fotoproteksi - Yousif, Emad; Al-Sayed, Raghda; Ahmed, Dena; Zainulabdeen, Khalid; Waleed, Reem; Bufaroosha, Muna; Hairunisa, Nany; Lestari, Ade Dwi; Widowati, Henie; Ridwan, Alvin Mohamad; Anestessia, Ira Juliet; Panduwati, Lira; Mayasari, Atut Cicih (Jurnal Biomedika dan Kesehatan, 2025)
Sunscreens are topical agents that protect the skin from the damaging effects of ultraviolet (UV) radiation, a major contributor to premature aging and skin cancer. These products are typically categorized into two main types: physical (inorganic or mineral) and chemical (organic) sunscreens. Physical sunscreens primarily consist of zinc oxide (ZnO) and titanium dioxide (TiO₂), which reflect and scatter UV rays, thereby providing broad-spectrum protection. Compared with chemical sunscreens, which absorb UV radiation and convert it into heat, inorganic agents are associated with a lower risk of systemic absorption and skin irritation, making them particularly suitable for sensitive skin and pediatric use. This review explores the fundamental mechanisms of action, formulation challenges, and comparative effectiveness of inorganic sunscreens. Special attention is given to their photostability, which contributes to longer-lasting protection, and to their safety profiles in both acute and chronic use. Additionally, recent innovations in nanoparticle technology have enhanced the aesthetic appeal of these agents by reducing visible residue. However, this has also raised new concerns about nanoparticle penetration and environmental impact. Finally, the review addresses public health considerations, including regulatory updates, consumer preferences, and the role of education in promoting informed use of sunscreen.